Cell Death Induction and Protection by Activation of Ubiquitously Expressed Anion/Cation Channels. Part 1: Roles of VSOR/VRAC in Cell Volume Regulation, Release of Double-Edged Signals and Apoptotic/Necrotic Cell Death - Okada, Yasunobu; Sabirov, Ravshan Z.; Sato-Numata, Kaori; Numata, Tomohiro (Frontiers in Cell and Developmental Biology, 2021)
Cell volume regulation (CVR) is essential for survival and functions of animal cells. Actually, normotonic cell shrinkage and swelling are coupled to apoptotic and necrotic cell death and thus called the apoptotic volume decrease (AVD) and the necrotic volume increase (NVI), respectively. A number of ubiquitously expressed anion and cation channels are involved not only in CVD but also in cell death induction. This series of review articles address the question how cell death is induced or protected with using ubiquitously expressed ion channels. The Part 1 foucusses on the roles of the volume-sensitive outwardly rectifying anion channels (VSOR), also called the volume-regulated anion channel (VRAC). VSOR is activated by cell swelling or reactive oxygen species (ROS) in a manner dependent on intracellular ATP. VSOR mediates volume-regulatory Cl− efflux and release of double-edged signaling molecles such as glutamate and gluthathione (GSH). VSOR activity is essentially involved not only in cell survival or protection from cell death by contributing to the regulatory volume decrease (RVD) coping with persistent cell swelling but also in induction of apoptotic cell death by mediating AVD-inducing Cl− efflux and GSH release. On the other hand, VSOR activity is doubly involved in excitotoxic neuronal necrosis both by mediating glutamate release from astrocytes and by mediating swelling-exaggerating Cl− influx driven by depolarization produced by activation of ionotropic glutamate receptors in neurons. Necrotic cell death is attained by NVI induction and RVD dysfunction. Under ATP-depleted conditions, mammalian cells exhibit persistant swelling because of impairment of ATP-dependent Na+-K+ pump activity, which plays a prerequisite role in steady-state CVR impinging on oncotic cell swelling due to the Donnan principle, and of inhibition of ATP-dependent VSOR activity. Under the conditions where acid and lactate are accumulated in the ischemic brain, called lactacidosis, VSOR activity and therefore the RVD event are abolished in glial and neuronal cells despite that prominent cell swelling is produced by uptake of Na+ and lactate−, thereby inducing NVI and necrotic cell death. VSOR was recently suggested to be somehow involved in activation of inflammasomes which is an essential event leading to one type of programmed necrosis, called pyroptosis.